EDUKASI MASYARAKAT PINGGIRAN SUNGAI DALAM PENANGANANAN KEGAWATDARURATAN JANTUNG PARU - hammad, hammad; Rizani, Khairir; Marwansyah, Marwansyah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
South Kalimantan is a watershed that has the highest number of people with cardiovascular disease in Indonesia. The community must certainly be prepared to face conditions in the event of a cardiovascular and pulmonary emergency. Community service is provided by providing health education on the concept of cardiopulmonary arrest to residents of Banjar Regency so that they can recognize signs of pulmonary heart emergency and be able to provide basic life support (BLS).. The results of the community service activities shows that the community is very enthusiastic and has the support of community leaders. It is very important to expand and involve more members of community groups in Banjar Regency so that an emergency preparedness community is formed.